OPTIMISING PHARMACY FINANCIAL MANAGEMENT: THE ROLE OF PHARMACISTS IN IMPROVING EFFICIENCY AND SUSTAINABILITY IN THE PHARMACEUTICAL BUSINESS - Gunawan Widjaja; Dyah Ersita Yustanti; Rio Johan Putra (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Optimising pharmacy financial management plays a crucial role in addressing the challenges of operational efficiency and business sustainability in the pharmaceutical industry amid increasingly competitive market conditions. As the primary managers, pharmacists have strategic responsibilities in planning, controlling, and reporting finances in a transparent and accountable manner. With good financial management—including budget planning, cash flow management, inventory control, and the use of information technology—pharmacists can minimise the risk of waste, maintain operational smoothness, and ensure business profitability. The active role of pharmacists also contributes to improving the quality of pharmaceutical services, the efficient use of resources, and adaptation to pharmaceutical business regulations, thereby becoming a key factor in maintaining the sustainability and competitiveness of pharmacies.